1999
DOI: 10.1103/physrevc.59.2351
|View full text |Cite
|
Sign up to set email alerts
|

γ transitions inA=7hypernuclei and a possible derivation of hypernuclear size

Abstract: On the basis of the ⌳ 5 HeϩNϩN three-body model which has successfully been applied to a systematic study of the energy and nucleon halo structure of the Aϭ7 isotriplet hypernuclei, strengths of ␥ transitions in ⌳ 7 Li and ⌳ 7 He are calculated. The new model confirms that the B(E2;5/2 ϩ →1/2 ϩ ) value in ⌳ 7 Li is reduced remarkably in comparison with the corresponding B(E2;3 ϩ →1 ϩ ) in the core nucleus 6 Li. This is due to the gluelike role of the ⌳ particle which induces a contraction of the core nuclear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
201
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(217 citation statements)
references
References 25 publications
16
201
0
Order By: Relevance
“…The calculation with NLSH-A parameter set also predicts spherical ground states for 13 Λ C and 23 Λ C. In the SHF calculations, the PES of 10 C with a prolate shape is so soft in the γ degree of freedom that one additional Λ drives the shape of 11 Λ C to be oblate [57]. In the present work, 11 Λ C is still prolate with a smaller β compared to 10 C. The addition of a Λ hyperon only makes the PES of 11 Λ C a little softer than that of 10 C. Similar situation holds for 17 Λ C. For the only triaxially deformed carbon nucleus, 18 C, it is observed that the Λ hyperon also makes the PES of 19 Λ C softer and the γ softness increases more towards the prolate direction. Since 20 C is strongly oblate deformed, the addition of a Λ hyperon does not change its shape much.…”
Section: Shape Polarization Effect Of λ Hyperon In Carbon Hypernucleimentioning
confidence: 86%
See 2 more Smart Citations
“…The calculation with NLSH-A parameter set also predicts spherical ground states for 13 Λ C and 23 Λ C. In the SHF calculations, the PES of 10 C with a prolate shape is so soft in the γ degree of freedom that one additional Λ drives the shape of 11 Λ C to be oblate [57]. In the present work, 11 Λ C is still prolate with a smaller β compared to 10 C. The addition of a Λ hyperon only makes the PES of 11 Λ C a little softer than that of 10 C. Similar situation holds for 17 Λ C. For the only triaxially deformed carbon nucleus, 18 C, it is observed that the Λ hyperon also makes the PES of 19 Λ C softer and the γ softness increases more towards the prolate direction. Since 20 C is strongly oblate deformed, the addition of a Λ hyperon does not change its shape much.…”
Section: Shape Polarization Effect Of λ Hyperon In Carbon Hypernucleimentioning
confidence: 86%
“…The softness of the PES of a nucleus in the γ direction can be measured by E po . For example, it is 0.74 MeV for 10 C and 0.34 MeV for 11 Λ C, which means that the PES of the latter is much softer than the former. However, this difference for 17 Λ C is only 0.06 MeV smaller than that for the corresponding core nucleus, which indicates a very tender change.…”
Section: Shape Polarization Effect Of λ Hyperon In Carbon Hypernucleimentioning
confidence: 99%
See 1 more Smart Citation
“…For the latter purpose, many theoretical works have been carried out in p-sd-pf shell Λ hypernuclei and revealed structure changes caused by the addition of a Λ particle, so-called impurity effects, such as changes of cluster structures [5][6][7][8][9][10][11][12][13][14] and deformation [15][16][17][18][19][20][21][22]. In particular, p-shell nuclei with pronounced clustering manifest drastic structure changes.…”
Section: Introductionmentioning
confidence: 99%
“…The measured energy spectra and electric multipole transition strengths in low-lying states have in fact provided rich information on the Λ-nucleon interaction in nuclear medium as well as on the impurity effect of Λ particle. Many theoretical methods have been developed to investigate the spectroscopy of hypernuclei, such as the cluster model [2,3], the shell model [4], the ab-initio method [5], the antisymmetrized molecular dynamics (AMD) [6], and self-consistent mean-field models [7,8]. Among them, the self-consistent mean-field approach is the only method which can be globally applied from light to heavy hypernuclei.…”
Section: Introductionmentioning
confidence: 99%